SARS-CoV-2 Nsp7 plays a role in cognitive dysfunction by impairing synaptic plasticity - Guo, Jiazheng; Li, WeiLing; Huang, Mengbing; Qiao, Jialu; Wan, Pin; Yao, Yulin; Ye, Lirui; Ding, Ye; Wang, Jianing; Peng, Qian; Liu, Wei; Xia, Yiyuan; et al. (Frontiers in Neuroscience, 2024)
It has been reported that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can result in long-term neurological symptoms such as cognitive dysfunction, however the specific mechanisms underlying this phenomenon remain unclear. Initially, we confirmed a reduction in the level of synaptic proteins in SH-SY5Y neurons following SARS-CoV-2 infection. SARS-CoV-2 Nsps are crucial for the efficient replication of the virus and play important roles in the interaction between virus and host cell. Nsps screening experiments implied that Nsp7 is able to reduce the level of synapsin-1. Furthermore, overexpression of Nsp7 in SH-SY5Y cells and mouse primary neurons demonstrated that Nsp7 could decrease the levels of synaptic proteins without affecting neuronal viability. Moreover, C57BL/6 mice receiving AAV-GFP-Nsp7 injections into the ventral hippocampus displayed impaired memory ability, along with reduced dendritic spine density and synaptic protein levels. Mechanistic investigations suggested that Nsp7-induced mitochondrial damage led to ROS production and ATP levels decreasing in neurons. Additional experiments employing the ROS inhibitor NAC demonstrated that Nsp7 suppressed the expression of synaptic proteins via ROS inducing, implicating mitochondrial dysfunction in synaptic plasticity impairment and subsequent cognitive dysfunction. Our findings underscore the crucial role of SARS-CoV-2 Nsp7 in cognitive dysfunction, which is potentially mediated through impaired synaptic plasticity via mitochondrial damage. This study enhances our understanding of the pathogenic mechanisms underlying central nervous system-related symptoms associated with SARS-CoV-2 infection.